Criteria Some Power Defined By Speed Endurance In Youth Basketball - Sami, Faris (Journal of Physical Education, 2016)
Basketball is one of the sports that depend on power defined by speed endurance as a major physical ability component. The problem of the research lays defining tests for power defined by speed endurance levels in basketball players. The subjects of the research were (99) basketball players from (Baghdad, the south region, Middle Forat region) for the season 2015 – 2016. The data for all (99) players was collected using proper statistical operations to come up with the results. The results showed that the test’s procedures were standardized for power defined by speed endurance in youth basketball players. In addition to that, the researchers concluded that power defined by speed endurance tests were applied for the first time in Iraq for youth basketball players. Finally the criteria of power defined by speed endurance test results were specified and defined.